Análise da correspodência entre as proporções de altura e largura do incisivo central superior e da face - MOREIRA, Lucas Lopes (2019)
Context: the aesthetic principles and parameters used for planning in prosthetic and restorative dentistry have been resulting in pleasant smiles. Objective: this work aims to analyze the biometric proportion of width and height of the maxillary central incisors in relation to the width and height of the face. Method: The research was executed through the measurement of width and height of the face and maxillary central incisors of 71 participants with a later statistical analysis of the obtained data. Results: The values of the proportion ratio between face and maxillary central incisors width, although moderated positive, were not statistically significant (p>0,05), however, the values of the proportion ratio between face and maxillary central incisor height were moderated positive and statistically significant (p<0,05). Conclusion: it is concluded that there is no tabulated and defined mathematical ratio relation between the horizontal and vertical measurements of the maxillary central incisors and the face.